Presence of Host-Plasma Membrane Type H(+)-ATPase in the Membrane Envelope Enclosing the Bacteroids in Soybean Root Nodules - Blumwald, Eduardo (1985)
An improved method is described for the isolation of membrane envelope enclosing the bacteroids (peribacteroid membrane) from soybean (Glycine max L.) root nodules. The ATPase activity of the peribacteroid membrane from infected roots is compared with that of the plasma membrane from uninfected roots. The two ATPases are similar in terms of their vanadate sensitivities, pH optima, and mineral cation requirements, and show antigenic cross-reactivity. However, the ATPase of peribacteroid membrane is more sensitive to stimulation by NH(4)(+). ATP-dependent proton translocation across the peribacteroid membrane was demonstrated in broken protoplasts of infected cells, by the use of fluorescence microscopy with acridine orange. It is suggested that acidification of the peribacteroid space by the peribacteroid membrane ATPase results in the conversion of NH(3) to NH(4)(+) in this space and thereby facilitates the removal of fixed-nitrogen from the bacteroid.